Method for recovering low-sulfur low-sodium iron phosphate from lithium iron phosphate black powder

Through acid immersion, copper -removing aluminum removal treatment and adjustment of phosphate iron Murbi and other steps, recover high -purity iron phosphate from the black powder black powder of waste lithium batteries, solve the problem of low product purity and large amount of water washing in existing technology, and achieve efficient water washing. Recycling process.

CN119370813APending Publication Date: 2025-01-28HUNAN TIANTAI TIANRUN NEW ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411663980.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In the prior art, when recovering iron phosphate from waste lithium battery black powder, the product has low purity, high impurity ion content, and large washing amount.

Method used

The acid immersion response was performed by contacting the slurry of lithium iron phosphate with water with the water of water, and then copper removal and aluminum removal treatment were performed to adjust the phosphate iron Murbi and pH value.

Benefits of technology

Effectively suppress the hydrolysis of iron phosphate and reduce the amount of impurities. The amount of water washing required for high-purity iron phosphate obtained was greatly reduced. The proportion of water washing to the product of the product was about 10-15: 1.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119370813A_ABST
    Figure CN119370813A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium battery recovery, and discloses a method for recovering low-sulfur low-sodium iron phosphate from lithium iron phosphate black powder. The method comprises the following steps: (1) contacting slurry I containing lithium iron phosphate black powder and water with inorganic acid to carry out acid leaching reaction, and carrying out solid-liquid separation to obtain a first liquid material; (2) sequentially carrying out copper removal treatment and aluminum removal treatment on the first liquid material, and carrying out solid-liquid separation to obtain a second liquid material; (3) contacting the second liquid with a phosphorus source I to obtain a third liquid material, adjusting the pH value of the third liquid material to pH 1, and carrying out solid-liquid separation to obtain a precipitate; and (4) contacting the slurry I containing the precipitate and water with a phosphorus source I to obtain a fourth liquid material, contacting the fourth liquid material with hydrogen peroxide to carry out oxidation reaction, and carrying out solid-liquid separation to obtain the iron phosphate. According to the method provided by the invention, the iron phosphate product with high purity and low impurity content can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium battery recycling, and in particular to a method for recycling low-sulfur and low-sodium iron phosphate from lithium iron phosphate black powder. Background Art

[0002] With the rapid development of new energy batteries, the market demand for lithium-ion batteries is also gradually increasing. Lithium iron phosphate materials stand out due to their low cost, good stability, high safety, long cycle life, and greener and more environmentally friendly than other materials. Iron phosphate is one of the key raw materials for synthesizing lithium iron phosphate materials, and its purity and quality will affect the electrochemical performance of lithium iron phosphate batteries.

[0003] The current mainstream preparation method for preparing iron phosphate products using waste lithium iron phosphate powder is similar to the above method. It is mainly divided into two categories. One is the full leaching method using inorganic acid for full leaching, followed by separation and purification of each element, or the selective lithium extraction method using a small amount of inorganic acid to leach lithium ions first, and then recovering elements such as phosphorus and iron. However, no matter which method is used, the iron phosphate prepared will inevitably adsorb or encapsulate some impurity ions. At the same time, the iron phosphate prepared by recycling waste lithium iron phosphate is in a mixed state in the solution from the beginning because the iron and phosphorus ions in the leaching solution are in a mixed state. This makes it extremely difficult to control the particle size and morphology of the obtained iron phosphate product by controlling the parameter conditions such as the addition rate of the phosphorus source or the iron source, as in the traditional iron phosphate production enterprises. As a result, the particle size of the iron phosphate prepared by waste lithium iron phosphate powder is extremely uneven and the agglomeration is serious. That is, the impurities in the product are more difficult to wash clean than the iron phosphate prepared by the above traditional method.

[0004] CN118026125A discloses a method for recovering iron phosphate for batteries from waste lithium iron phosphate battery black powder. The method comprises the following steps: subjecting the waste lithium iron phosphate battery black powder to an acid leaching treatment, removing impurities from the acid leaching liquid to remove copper, aluminum and titanium therein, and then subjecting the acid leaching liquid to oxidation precipitation, aging and calcination in sequence to obtain iron phosphate for batteries. However, the method has the defect that a large amount of water is used for washing the iron phosphate during the recovery process.

[0005] CN113479861A reduces the amount of washing water by adding a surfactant (such as hexadecyltrimethylammonium bromide and polyvinylpyrrolidone) to the solution to prepare iron phosphate with uniform particle size and small agglomeration. However, in this way, since organic matter is introduced into the solution, subsequent wastewater treatment is a more troublesome problem; at the same time, organic matter that may be entrained in the product affects the purity of the product, and the amount of surfactant required by this method is large, and the cost is high.

[0006] It has also been reported that iron phosphate can be washed to remove impurities by adding phosphoric acid, phosphate or citric acid to the washing water, but when adding phosphoric acid or phosphate, the subsequent wastewater contains a large amount of phosphate ions, which is difficult to handle. Citric acid has almost no effect on the washing of impurities in products prepared by adjusting the pH with liquid alkali. Summary of the invention

[0007] The purpose of the present invention is to solve the problems of low purity and high impurity ion content of iron phosphate prepared by using waste lithium battery black powder in the prior art.

[0008] In order to achieve the above object, the present invention provides a method for recovering low-sulfur and low-sodium iron phosphate from lithium iron phosphate black powder, the method comprising the following steps:

[0009] (1) contacting a slurry I containing lithium iron phosphate black powder and water with an inorganic acid to perform an acid leaching reaction, and obtaining a first liquid material through solid-liquid separation;

[0010] The lithium iron phosphate black powder has a lithium content of 2.3-4.08 wt %, a copper content of no more than 2 wt %, and an aluminum content of no more than 2.5 wt %;

[0011] (2) subjecting the first liquid material to copper removal treatment and aluminum removal treatment in sequence, and obtaining a second liquid material through solid-liquid separation;

[0012] (3) contacting the second liquid with a phosphorus source I to obtain a third liquid material, and adjusting the pH value of the third liquid material to pH 1, and obtaining a precipitate by solid-liquid separation; the pH 1 is 4.5-5.0;

[0013] The phosphorus source I is added in an amount such that the phosphorus-iron molar ratio of the third liquid material is 1.2-1.5:1;

[0014] (4) contacting the slurry ⅠⅠ containing the precipitate and water with a phosphorus source ⅠⅠ to obtain a fourth liquid material, and contacting the fourth liquid material with hydrogen peroxide to perform an oxidation reaction, and obtaining the iron phosphate through solid-liquid separation;

[0015] Wherein, in step (2), the aluminum removal step includes:

[0016] (S1) Under an inert atmosphere, adjusting the pH value of the product of the copper removal treatment to pH 2 to obtain a mixed solution I;

[0017] (S2) adjusting the pH value of the mixed solution I to pH 3, contacting and mixing the obtained mixed solution II with sodium fluoride, and obtaining the second liquid material through solid-liquid separation; relative to 1g of the lithium iron phosphate black powder, the amount of the sodium fluoride is 0.01-0.04g.

[0018] Through the above technical solution, the present invention has at least the following advantages:

[0019] The method provided by the present invention can effectively inhibit the hydrolysis of ferric phosphate during the recovery process and reduce the adsorption amount of impurities; the ratio of the amount of washing water to the dry basis of the product for the recovered high-purity ferric phosphate is about 10-15:1, which is much lower than the amount of washing water (40-60:1) of the recovery method in the prior art;

[0020] In summary, the method provided by the present invention can not only obtain high-purity iron phosphate, but also greatly reduce the amount of washing water required by the method provided by the present invention compared with the traditional method. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is a physical picture of the precipitate and iron phosphate obtained in Example 1 of the present invention;

[0022] Figure 2 is the XRD pattern of the precipitate obtained in Example 1 of the present invention;

[0023] Figure 3 This is the XRD diagram of the iron phosphate obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0024] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0025] In the present invention, the lithium iron phosphate black powder includes but is not limited to battery powder obtained by crushing and screening batteries with or without liquid injection, lithium iron phosphate pole piece powder, lithium iron phosphate degraded material, and the like.

[0026] As mentioned above, the present invention provides a method for recovering low-sulfur and low-sodium iron phosphate from lithium iron phosphate black powder, the method comprising the following steps:

[0027] (1) contacting a slurry I containing lithium iron phosphate black powder and water with an inorganic acid to perform an acid leaching reaction, and obtaining a first liquid material through solid-liquid separation;

[0028] The lithium iron phosphate black powder has a lithium content of 2.3-4.08 wt %, a copper content of no more than 2 wt %, and an aluminum content of no more than 2.5 wt %;

[0029] (2) subjecting the first liquid material to copper removal treatment and aluminum removal treatment in sequence, and obtaining a second liquid material through solid-liquid separation;

[0030] (3) contacting the second liquid with a phosphorus source I to obtain a third liquid material, and adjusting the pH value of the third liquid material to pH 1, and obtaining a precipitate by solid-liquid separation; the pH 1 is 4.5-5.0;

[0031] The phosphorus source I is added in an amount such that the phosphorus-iron molar ratio of the third liquid material is 1.2-1.5:1;

[0032] (4) contacting the slurry ⅠⅠ containing the precipitate and water with a phosphorus source ⅠⅠ to obtain a fourth liquid material, and contacting the fourth liquid material with hydrogen peroxide to perform an oxidation reaction, and obtaining the iron phosphate through solid-liquid separation;

[0033] Wherein, in step (2), the aluminum removal step includes:

[0034] (S1) Under an inert atmosphere, adjusting the pH value of the product of the copper removal treatment to pH 2 to obtain a mixed solution I;

[0035] (S2) adjusting the pH value of the mixed solution I to pH 3, contacting and mixing the obtained mixed solution II with sodium fluoride, and obtaining the second liquid material through solid-liquid separation; relative to 1g of the lithium iron phosphate black powder, the amount of the sodium fluoride is 0.01-0.04g.

[0036] The inventors of the present invention unexpectedly discovered during the research process that by reversing the precipitation and oxidation steps in the iron phosphate recovery process, that is, adjusting the iron-phosphorus ratio of the solution after aluminum removal and continuing to adjust the pH value, the phosphorus and iron ions in the solution are precipitated in the form of ferrous phosphate octahydrate, which is then washed, the iron-phosphorus ratio is adjusted a second time and oxidized, and finally high-purity iron phosphate can be obtained; and the amount of washing water required for the above operation process to obtain high-purity iron phosphate is greatly reduced.

[0037] Preferably, in step (1), the content of fluorine in the lithium iron phosphate black powder is not higher than 1.5 wt %.

[0038] Preferably, in step (1), the amount of the inorganic acid used is 0.5-1.0 g relative to 1 g of the lithium iron phosphate black powder.

[0039] Preferably, in step (1), the pH value of the first liquid material is 0.8-1.2.

[0040] Preferably, the conditions of the acid leaching reaction include: a rotation speed of 80-100 rpm, a temperature of 50-70° C., and a time of 0.5-12 h. The inventors found that in this preferred case, the technical solution provided by the present invention can obtain iron phosphate with higher purity and lower impurity ion content.

[0041] Preferably, in step (1), in the slurry I, the weight ratio of the lithium iron phosphate black powder to the water is 1:3-5.

[0042] Preferably, in step (2), iron powder is added to perform the copper removal treatment, and the amount of the iron powder is 0.005-0.02 g relative to 1 g of the lithium iron phosphate black powder.

[0043] Preferably, in step (2), the pH2 is 2.5-3.5.

[0044] Preferably, in step (2), the pH3 is 1.5-2.0.

[0045] Preferably, in step (2), the amount of sodium fluoride used is 0.02-0.03 g relative to 1 g of the lithium iron phosphate black powder.

[0046] Preferably, in step (S1), the pH adjuster used to adjust the pH value of the first liquid material is selected from at least one of liquid alkali, ammonia water, sodium carbonate, lithium carbonate and lithium hydroxide, preferably liquid alkali.

[0047] Preferably, the concentration of the liquid caustic soda is 20-50wt%.

[0048] Preferably, in step (S1), the inert atmosphere is nitrogen or argon.

[0049] According to a preferred specific embodiment, the aluminum removal step also includes: in step (S1), the product after adjusting the pH value of the first liquid material is stirred and mixed before solid-liquid separation, and the stirring and mixing conditions include: temperature of 25-55°C and time of 0.5-2h.

[0050] Preferably, in step (S2), the pH adjuster used to adjust the pH value of the mixed solution I is selected from at least one of hydrochloric acid, sulfuric acid, nitric acid and phosphoric acid, preferably sulfuric acid.

[0051] Preferably, the contact mixing conditions include: temperature of 25-55° C. and time of 0.5-2 h.

[0052] Preferably, the inorganic acid is selected from at least one of hydrochloric acid, sulfuric acid, nitric acid and phosphoric acid, preferably sulfuric acid.

[0053] Preferably, the phosphorus source I and the phosphorus source II are each independently selected from at least one of phosphoric acid, sodium phosphate, ammonium phosphate and lithium phosphate, preferably sodium phosphate and / or phosphoric acid.

[0054] Preferably, in step (3), the pH adjusting agent used to adjust the pH value of the third liquid material is selected from at least one of liquid alkali, ammonia water, sodium carbonate, lithium carbonate and lithium hydroxide, preferably liquid alkali.

[0055] According to a preferred specific embodiment, the method further comprises: in step (3), before solid-liquid separation, the product after adjusting the pH value of the third liquid material is stirred and mixed, and the stirring and mixing conditions include: temperature of 25-55°C and time of 0.5-2h.

[0056] Preferably, the method further comprises: in step (3), washing the precipitate at least twice and then performing liquid-solid separation, and then contacting the obtained filter cake and water slurry ⅠⅠ with phosphorus source ⅡⅠ to obtain the fourth liquid material.

[0057] Preferably, water is used for the washing, and the liquid-to-solid ratio of the washing is 2-5:1.

[0058] Preferably, the washing conditions include: a temperature of 25-80° C. and a washing time of 1-5 h / time.

[0059] Preferably, in step (4), the amount of the phosphorus source II added is such that the phosphorus to iron molar ratio of the fourth liquid material is 0.96-1: 1. In this preferred embodiment, the technical solution provided by the present invention can obtain iron phosphate with higher purity and lower impurity ion content.

[0060] Preferably, in step (4), the amount of hydrogen peroxide used is 0.02-0.26 g relative to 1 g of the lithium iron phosphate black powder.

[0061] Preferably, in step (4), in the slurry Ⅱ, the weight ratio of the precipitate to the water is 1:2-4.

[0062] Preferably, the oxidation reaction conditions include: temperature of 25-60° C. and time of 1-5 h.

[0063] The present invention will be described in detail below by way of examples.

[0064] In the following examples, unless otherwise specified, the instruments, reagents, materials, etc. involved are all conventional instruments, reagents, materials, etc., which can be obtained through conventional commercial channels. In particular, unless otherwise specified, the reagents used are all commercially available analytically pure products.

[0065] Lithium iron phosphate black powder (H-1): Sourced from Hunan Anhua Tyson Recycling Technology Co., Ltd., the lithium content is 2.8wt%, the copper content is 0.5wt%, the aluminum content is 1.5wt%, the fluorine content is 0.5wt%, and the content of other elements is 94.7wt%.

[0066] Lithium iron phosphate black powder (H-2): Sourced from Hunan Bangpu Recycling Technology Co., Ltd., the lithium content is 4.08wt%, the copper content is 0.1wt%, the aluminum content is 0.5wt%, the fluorine content is 0.01wt%, and the content of other elements is 95.31wt%.

[0067] In the following examples, the relevant characteristic parameters are measured by the following methods:

[0068] (1) Sodium and sulfate content test: The results were obtained by using an iCAP PRO X Duo Thermo Fisher Scientific inductively coupled plasma optical emission spectrometer.

[0069] (2) Micromorphology: obtained by scanning electron microscope (SEM) test using Hitachi S4800.

[0070] (3) XRD spectrum: The XRD pattern was tested using a SMART LAB / 3KW XRD-X-ray powder diffractometer. The test conditions were: Cu target X-ray tube, scanning range of 10° to 80°, and scanning speed of 10° / min.

[0071] (4) Purity of iron phosphate: measured using iCAP PRO X Duo Thermo Fisher Scientific inductively coupled plasma optical emission spectrometer.

[0072] (6) Iron-phosphorus molar ratio: obtained by testing according to the method in HG / T 4701-2021 standard.

[0073] Example 1

[0074] (1) Under stirring conditions, slurry I containing lithium iron phosphate black powder (500 g) and pure water was contacted with an inorganic acid (sulfuric acid with a concentration of 98 wt %) in an amount of 0.6 g / g lithium iron phosphate black powder to perform an acid leaching reaction (rotation speed of 100 rpm, temperature of 50° C., and time of 0.5 h), and a first liquid material (pH value of 0.8) was obtained by solid-liquid separation (filtration);

[0075] (2) Under stirring conditions at room temperature, slowly add iron powder (0.01 g / g lithium iron phosphate black powder) to the first liquid material to perform copper removal treatment (time is 20 min) to ensure that copper ions are completely removed from the solution, and continue to filter the solution to obtain a copper removal solution;

[0076] Under an inert atmosphere (nitrogen), the pH value of the copper removal product (the aforementioned copper removal solution) was adjusted to pH 2 (pH 2 was 3.0) with 32 wt % of liquid alkali to remove aluminum once, and after stirring and mixing (temperature was 40° C., time was 0.5 h), solid-liquid separation (filtration) was performed to obtain a mixed solution I;

[0077] The pH value of the mixed solution I is adjusted to pH 3 (pH 3 is 1.8) using sulfuric acid with a concentration of 98 wt %, and the obtained mixed solution ⅠⅠ is contacted and mixed with sodium fluoride (temperature is 40° C., time is 0.5 h) to remove aluminum for the second time, and a second liquid material is obtained by solid-liquid separation;

[0078] (3) contacting the second liquid with phosphorus source I (sodium phosphate) to obtain a third liquid material, and adding liquid alkali to continue adjusting the pH value of the third liquid material to pH 1, stirring and mixing (temperature of 50° C., time of 0.5 h), and then separating the solid and the liquid (filtering) to obtain a precipitate;

[0079] (4) The precipitate was washed with pure water at a liquid-to-solid ratio of 3:1 (temperature of 50°C, 2h / time) twice, followed by liquid-solid separation (filtration) to obtain a filter cake; then, under continuous stirring, the slurry ⅠⅠ containing the filter cake and pure water was contacted with a phosphorus source ⅠⅠ (phosphoric acid) to obtain a fourth liquid material, and the fourth liquid material was contacted with hydrogen peroxide (0.15g / g lithium iron phosphate black powder) to perform an oxidation reaction, and after solid-liquid separation (filtration), it was placed in an oven at 105°C and dried for 24h to obtain iron phosphate.

[0080] The raw material ratio and process conditions are shown in Table 1.

[0081] Unless otherwise specified, Examples 2 and 3 are carried out using a method similar to that of Example 1, except that different raw material ratios and process conditions are used. For details, see Table 1.

[0082] Table 1

[0083]

[0084] Note: Weight ratio 1 is the weight ratio of lithium iron phosphate black powder to pure water in slurry Ⅰ; weight ratio 2 is the weight ratio of lithium iron phosphate black powder to pure water in slurry ⅠⅠ.

[0085] Example 4

[0086] This embodiment is carried out in a similar manner to that of Embodiment 1, except that the amount of lithium iron phosphate black powder in this embodiment is kept unchanged, and the amount of sodium fluoride is adjusted to 0.01 g / g lithium iron phosphate black powder to obtain iron phosphate.

[0087] Example 5

[0088] This example is carried out in a manner similar to that of Example 1, except that the conditions of step (4) in this example are different; specifically, in step (4), the amount of phosphorus source ⅠⅠ added is such that the molar ratio of phosphorus to iron in the fourth liquid material is 1.2:1, thereby obtaining iron phosphate.

[0089] Comparative Example 1

[0090] This comparative example is carried out using a method similar to that of Example 1, except that the conditions of step (3) in this comparative example are different; specifically, in step (3), pH 1 is 4.0, and iron phosphate is obtained.

[0091] Comparative Example 2

[0092] This comparative example was carried out in a similar manner to Example 1, except that the amount of lithium iron phosphate black powder in this comparative example was kept unchanged, and the amount of sodium fluoride was adjusted to 0.005 g / g lithium iron phosphate black powder to obtain iron phosphate.

[0093] Comparative Example 3

[0094] This comparative example was carried out in a similar manner to Example 1, except that step (3) was not carried out and step (4) was different. Step (4) was specifically as follows:

[0095] Under continuous stirring, the second liquid material is contacted with phosphorus source ⅠⅠ (phosphoric acid) to obtain a fourth liquid material, and the fourth liquid material is contacted with hydrogen peroxide (0.15 g / g lithium iron phosphate black powder) to carry out an oxidation reaction. The product obtained by the oxidation reaction is washed with pure water at a liquid-to-solid ratio of 3:1 (temperature of 80°C, 2h / time) for 3 times, and placed in an oven at 105°C for 24h to obtain iron phosphate.

[0096] Test Case

[0097] The purity, sodium content, sulfate content and aluminum content of the iron phosphate prepared in the above example were tested, and the ratio of the amount of washing water in the method to the dry basis of the product (the dry basis of the product refers to the iron phosphate product after drying) was calculated. At the same time, according to "Iron Phosphate for Batteries" (HG / T 4701-2021), the content of each main element in the iron phosphate product was evaluated to see whether it met the battery grade standard. The specific results are shown in Table 2.

[0098] Table 2

[0099]

[0100]

[0101] The present invention Figure 1 The actual picture of the precipitate and iron phosphate obtained in Example 1 is provided as an example; Figure 1 In the figure, the precipitate before oxidation washing is blue, and the iron phosphate after oxidation washing is grayish white, which shows that the method of the present invention obtains a precipitate after the third pH adjustment and performs oxidation washing on the material, which can change the type of material.

[0102] The present invention Figure 2 The XRD pattern of the precipitate obtained in Example 1 is provided as an example; Figure 2 By comparing with the standard card PDF#30-0662 of ferrous phosphate octahydrate, it can be known that the method of the present invention obtains the intermediate product ferrous phosphate octahydrate. Therefore, in the method of the present invention, the intermediate product obtained before the oxidation reaction (washing) does not contain trivalent iron, which can effectively avoid the adsorption and entrainment of impurity elements caused by the hydrolysis of trivalent iron during solid-liquid separation.

[0103] The present invention Figure 3 The XRD pattern of the iron phosphate obtained in Example 1 is exemplarily provided in Figure 3 By comparing with the standard card PDF#50-1635 of iron phosphate, it can be seen that the method of the present invention successfully obtains an iron phosphate product with higher purity. Therefore, in the method of the present invention, the intermediate product ferrous phosphate octahydrate can be converted into a high-purity target product iron phosphate after oxidation reaction (washing).

[0104] It can be seen from the above results that the method provided by the present invention can obtain an iron phosphate product with high purity and low impurity content; in addition, compared with the traditional method, the method provided by the present invention also greatly reduces the amount of washing water required.

[0105] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for recovering low-sulfur and low-sodium iron phosphate from lithium iron phosphate black powder, characterized in that: The method comprises the following steps: (1) contacting a slurry I containing lithium iron phosphate black powder and water with an inorganic acid to perform an acid leaching reaction, and obtaining a first liquid material through solid-liquid separation; The lithium iron phosphate black powder has a lithium content of 2.3-4.08 wt %, a copper content of no more than 2 wt %, and an aluminum content of no more than 2.5 wt %; (2) subjecting the first liquid material to copper removal treatment and aluminum removal treatment in sequence, and obtaining a second liquid material through solid-liquid separation; (3) contacting the second liquid with a phosphorus source I to obtain a third liquid material, and adjusting the pH value of the third liquid material to pH 1, and obtaining a precipitate by solid-liquid separation; the pH 1 is 4.5-5.0; The phosphorus source I is added in an amount such that the phosphorus-iron molar ratio of the third liquid material is 1.2-1.5:1; (4) contacting the slurry ⅠⅠ containing the precipitate and water with a phosphorus source ⅠⅠ to obtain a fourth liquid material, and contacting the fourth liquid material with hydrogen peroxide to perform an oxidation reaction, and obtaining the iron phosphate through solid-liquid separation; Wherein, in step (2), the aluminum removal step includes: (S1) Under an inert atmosphere, adjusting the pH value of the product of the copper removal treatment to pH 2 to obtain a mixed solution I; (S2) adjusting the pH value of the mixed solution I to pH 3, contacting and mixing the obtained mixed solution II with sodium fluoride, and obtaining the second liquid material through solid-liquid separation; relative to 1g of the lithium iron phosphate black powder, the amount of the sodium fluoride is 0.01-0.04g.

2. The method according to claim 1, wherein: In step (1), the amount of the inorganic acid used is 0.5-1.0 g relative to 1 g of the lithium iron phosphate black powder; And / or, the conditions of the acid leaching reaction include: a rotation speed of 80-100 rpm, a temperature of 50-70° C., and a time of 0.5-12 h.

3. The method according to claim 1, wherein: In step (1), in the slurry I, the weight ratio of the lithium iron phosphate black powder to the water is 1:3-5.

4. The method according to any one of claims 1 to 3, wherein: In step (2), iron powder is added to perform the copper removal treatment, and the amount of the iron powder is 0.005-0.02 g relative to 1 g of the lithium iron phosphate black powder.

5. The method according to any one of claims 1 to 3, wherein: In step (2), the pH2 is 2.5-3.5; and / or the pH3 is 1.5-2.

0.

6. The method according to claim 5, wherein: In step (2), the amount of sodium fluoride used is 0.02-0.03 g relative to 1 g of the lithium iron phosphate black powder.

7. The method according to any one of claims 1 to 3, wherein: The inorganic acid is selected from at least one of hydrochloric acid, sulfuric acid, nitric acid and phosphoric acid; And / or, the phosphorus source I and the phosphorus source II are each independently selected from at least one of phosphoric acid, sodium phosphate, ammonium phosphate and lithium phosphate.

8. The method according to any one of claims 1 to 3, wherein: In step (4), the amount of the phosphorus source II added is such that the molar ratio of phosphorus to iron in the fourth liquid material is 0.96-1:

1.

9. The method according to any one of claims 1 to 3, wherein: In step (4), the amount of hydrogen peroxide used is 0.02-0.26 g relative to 1 g of the lithium iron phosphate black powder.

10. The method according to any one of claims 1 to 3, wherein: In step (4), in the slurry ⅠⅠ, the weight ratio of the precipitate to the water is 1:2-4; And / or, the conditions of the oxidation reaction include: temperature of 25-60° C. and time of 1-5 h.

Citation Information

Patent Citations

  • Preparation method of nano iron phosphate with low sulfur content

    CN113479861A

  • Method for recycling iron phosphate for batteries from black powder of waste lithium iron phosphate batteries

    CN118026125A